2021
DOI: 10.21037/qims-20-700
|View full text |Cite
|
Sign up to set email alerts
|

Change in left ventricular velocity time integral during Trendelenburg maneuver predicts fluid responsiveness in cardiac surgical patients in the operating room

Abstract: Background: Fluid responsiveness is an important topic for clinicians. We investigated whether changes in left ventricular outflow tract (LVOT) velocity time integral (VTI) during a Trendelenburg position (TP) maneuver can predict fluid responsiveness as a non-invasive marker in coronary artery bypass graft (CABG) surgery patients in the operating room. Methods: This prospective, single-center observational study, performed in the operating room, enrolled 65 elective CABG patients. Hemodynamic data coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Note that some other tests like EEO and Vt challenge might also be suitable in the case of prone positioning. Similar results with the Trendelenburg manoeuvre have been described in patients under veno-arterial extracorporeal membrane oxygenation [ 92 ] and during the surgical intervention [ 93 ].…”
Section: Other Testssupporting
confidence: 82%
“…Note that some other tests like EEO and Vt challenge might also be suitable in the case of prone positioning. Similar results with the Trendelenburg manoeuvre have been described in patients under veno-arterial extracorporeal membrane oxygenation [ 92 ] and during the surgical intervention [ 93 ].…”
Section: Other Testssupporting
confidence: 82%
“…We did not measure the SV ∆ during head-down positioning, thus we cannot know for certain the functional cardiac state of the healthy subjects we studied. Nevertheless, Trendelenburg is a well-accepted means of increasing preload and testing functional hemodynamics [36,37,56]. In addition, we found a strong relationship between SV ∆ and ccFT ∆ in this population; a +2% ccFT ∆ threshold is an excellent surrogate for +10% SV ∆ [23,24,26].…”
Section: Discussionmentioning
confidence: 50%
“…Trendelenburg positioning is reported to accurately predict patients who respond to intravenous fluid administration; however, the maneuver itself is variably practiced. For example, Ma and colleagues moved patients from 15 degrees head above the horizontal to 15 degrees below; this resulted in an excellent diagnostic accuracy with 100% sensitivity [36]. On the other hand, Terai and colleagues performed the maneuver by comparing the horizontal (i.e., supine) to head-down in healthy subjects [37].…”
Section: Discussionmentioning
confidence: 99%
“…[45] Although several studies have reported that the LVOT-VTI can predict fluid responsiveness, it has some limitations, including severe aortic regurgitation or obstruction, arrhythmias, and severe measurement errors. [46,47] However, Vignon et al [48] compared several ultrasound indicators to monitor fluid responsiveness in mechanically ventilated patients and found that LVOT-VTI had the highest sensitivity to measure the diameter of the superior vena cava, while respiratory variability had the highest specificity, which was better than IVC-related measures and LVOT-VTI. For improved accuracy, appropriate measures should be taken according to their characteristics, and more than one measure should be used to assess fluid responsiveness.…”
Section: Discussionmentioning
confidence: 99%